Analisis Technological Pedagogical and Content Knowledge (TPACK) Mahasiswa Calon Guru SD Pada Materi IPA - Yanti, Meili; Mawarwati (Elementary Teacher Education Program, Majalengka University, 2023)
In the recent decades, teacher’s competencies has been one of the major interesting research subjects ini education due to technology improvement. Therefore the teacher study program can be a place to reflect on these abilities, called TPACK. In this study, TPACK ability of preservice teachers was investigated. By applying decriptive methods among 50 students were participated in this study. Selection of participants using the convenience sampling method. The sample selection method is based on the availability of elements and the ease of obtaining them. The convenience sampling method was carried out because the study used elementary school teacher education study program students and there were 2 classes of 50 participants. The data in this study were obtained by using a questionnaire on student perceptions about their TPACK abilities. This instrument was developed by Schmidt (2009) which consists of 30 statement items. The results reveals that TPACK ability of preservice elementary school teachers in science material is quite good. The results of this study can provide a reference for the curriculum development of the PGSD Study Program to be used as a feature of the PGSD Study Program. If you want to focus on developing the TPACK of preservice teachers, then in the future the courses in the program must be able to support the achievement of these TPACK abilities.